2021
DOI: 10.3390/s21041463
|View full text |Cite
|
Sign up to set email alerts
|

SDNN24 Estimation from Semi-Continuous HR Measures

Abstract: The standard deviation of the interval between QRS complexes recorded over 24 h (SDNN24) is an important metric of cardiovascular health. Wrist-worn fitness wearable devices record heart beats 24/7 having a complete overview of users’ heart status. Due to motion artefacts affecting QRS complexes recording, and the different nature of the heart rate sensor used on wearable devices compared to ECG, traditionally used to compute SDNN24, the estimation of this important Heart Rate Variability (HRV) metric has neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These devices allow for a complete and objective overview of the users’ health status by passively recording semi-continuous heart rate, heart rate variability, blood oxygenation, steps, sedentary behaviours, and sleep quality. The recent literature validate the data provided by wrist-worn devices, establishing the profile error of the heart rate (HR) and heart rate variability (HRV) measurements [ 67 , 68 , 69 , 70 , 71 ]. Therefore, these devices allow for the objective and passive evaluate the well-being and recovery status of players in order to produce a potential index of injury risk.…”
Section: Data Descriptionmentioning
confidence: 92%
“…These devices allow for a complete and objective overview of the users’ health status by passively recording semi-continuous heart rate, heart rate variability, blood oxygenation, steps, sedentary behaviours, and sleep quality. The recent literature validate the data provided by wrist-worn devices, establishing the profile error of the heart rate (HR) and heart rate variability (HRV) measurements [ 67 , 68 , 69 , 70 , 71 ]. Therefore, these devices allow for the objective and passive evaluate the well-being and recovery status of players in order to produce a potential index of injury risk.…”
Section: Data Descriptionmentioning
confidence: 92%
“…In addition, previous research indicated that the ultra-low and very low frequencies of the HRV spectra over 24 hours had a characteristic of 1/f shape that comes from the activity of the sinoatrial node [181]; While the ANS contribution might be modelled as a stochastic process of white noise with two periodic components at the characteristics baroreceptor and respiratory peaks in the low-and high-frequency bands [5]. However, it is noted that the shape of the spectrum may be altered due to measurement uncertainties, for example, the presence of missing data dampens low frequencies and enhances high frequencies [151].…”
Section: Uncertainty Characterisation and Quantification A Characteri...mentioning
confidence: 99%